Prenatal Diagnosis and Postnatal Outcome of Fetal Ovarian Cysts - Mehmet Serdar Kütük; Mehmet Dolanbay; Mahmut Tuncay Özgün; Menşure Tonguç; Mustafa Başbuğ (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: The aim of the present study was to assess the ultrasonographic features, clinical characteristic, and neonatal outcome in fetuses with ovarian cyst. STUDY DESIGN: Retrospective analysis of nine cases of fetal ovarian cyst diagnosed antenatally with regard to ultrasonographic finding, clinical course, and postnatal outcome. RESULTS: Nine cases were diagnosed as having fetal ovarian cysts antenatally. The age of antenatal diagnoses ranged between 30-36 gestational weeks’. One case had (1/9, 11%) additional anomaly (Double collecting system). The cysts were unilateral in all cases. In one case the giant ovarian cyst was drained antenatally due to its compressive effects. Two cases were operated postnatally because of ovarian torsion (2/9, 22.2%). One case had persistent ovarian cyst which showed some degree of regression postnatally. One case regressed before birth, and remaining four cases completely vanished during postnatal follow- up (4/9, 44.4%). CONCLUSION: The most probable outcome for fetal ovarian cysts is spontaneous resolution. Unless complicated with torsion and haemorrhage, close ultrasonographic follow- up is to be recommended.